pengaruh disiplin kerja dan lingkungan kerja terhadap kinerja karyawan divisi assembling finishing PT. Kmk Global Sport - setiawati, devi (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2024)
This study aims to test, review and analyze the relationship between the success of various activities in the company to achieve its goals not only depends on the superiority of the existing technology system or facilities owned, but is also greatly determined by the role of human resources in the company in the application of Work Discipline and Work Environment to Employee Performance at PT. KMK Global Sport. This study involved 70 respondents and used a quantitative descriptive method. Data analysis was carried out using the Statistical Package for Social Science (SPSS) version 20, with statistical tests in the form of multiple linear regression. The results of the analysis show that partially and simultaneously (F Test), the F-count value of 44.690> F-table 3.13, it can be concluded that simultaneously it has a signiϔicant effect on the dependent variable and the t-test results in the study also show that two independent variables, namely work discipline and work environment, have a positive and signiϔicant effect on the dependent variable. For the work discipline variable, the signiϔicance value is 0.000 <0.05, and the t-count value is 6.518> t-table 1.997. Likewise with the work environment variable, the signiϔicance value is 0.000 < 0.05, with a t-count value of 9.391 > 1.997. This supports the hypothesis that both variables have a signiϔicant impact on the results measured in this study.